2015
DOI: 10.1021/nl503697c
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermally Synthesized Sb2Te3 Platelets Show Unexpected Optical Contrasts in Mid-Infrared Near-Field Scanning Microscopy

Abstract: We report nanoscale-resolved optical investigations on the local material properties of Sb2Te3 hexagonal platelets grown by solvothermal synthesis. Using mid-infrared near-field microscopy, we find a highly symmetric pattern, which is correlated to a growth spiral and which extends over the entire platelet. As the origin of the optical contrast, we identify domains with different densities of charge carriers. On Sb2Te3 samples grown by other means, we did not find a comparable domain structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 48 publications
2
41
1
Order By: Relevance
“…It is worth emphasizing that these patterns differ from the optical contrast in Sb 2 Te 3 platelets reported in previous studies. [27] There, the pattern is closely related to the spiral growth, with a topographically rough surface with screw dislocations, whereas in our system, the surface is flat, with no association of a screw dislocation with the formation of the optical patterns.…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…It is worth emphasizing that these patterns differ from the optical contrast in Sb 2 Te 3 platelets reported in previous studies. [27] There, the pattern is closely related to the spiral growth, with a topographically rough surface with screw dislocations, whereas in our system, the surface is flat, with no association of a screw dislocation with the formation of the optical patterns.…”
Section: Introductionmentioning
confidence: 49%
“…[27,33,34] Considering that IR s-SNOM is sensitive to low-energy intra-and interband transitions, Drude conductivity, and related surface excitations, we performed broadband spectroscopic nanoimaging using synchrotron near-field infrared nanospectroscopy (SINS) [35] from 750 to 2000 cm −1 . (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…The region of largest near‐field phase contrast extends to the left of the TD, and exhibits a corresponding change in contrast in both the ECCI and SE images, but with no observable corresponding topographic feature identified in the AFM topography image. Previous s‐SNOM investigations have shown that variations in strain,27b charge‐carrier concentration,25a and polytype27a can induce such effects in the near‐field contrasts. In ECCI however, such a bright‐line charge contrast as is highlighted in Figure a is known to be due to subsurface strain, most likely caused by the nucleation point of the TD inducing the carrot defect.…”
Section: Resultsmentioning
confidence: 96%
“…To extract the spectral response, the sample can be probed at multiple discrete incident frequencies of the focused laser in succession to plot the frequency‐dependent s‐SNOM amplitude and/or phase, providing a map of the spatial variation in the s‐SNOM response at each frequency 22b. Thus, s‐SNOM provides obvious benefits for high resolution defect imaging when monitored at mid‐IR frequencies as it provides the potential to i) investigate the impact of defects upon the free‐carrier density or polaritonic behaviors, ii) provide information regarding crystalline structure and polytype, and iii) determine the role such defects play in the performance of nanophotonic devices such as polaritonic antennas, waveguides, and metasurfaces . While s‐SNOM should not be expected to replace the previously mentioned spectroscopic and microscopic methods, it instead provides a noninvasive technique offering complementary IR spectroscopic information about the defect(s) and surrounding regions of interest, while simultaneously imaging the topography of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12,14–16 ] Because of the variability of their electrical properties (mainly resistance), PCMs have been widely used in nonvolatile electric fields, such as high‐density memories. [ 17–23 ] Because of the variability of their optical properties (mainly optical constants, [ 9,24,25 ] reflectivity, [ 26,27 ] transmission, [ 25,28,29 ] absorption, [ 30,31 ] and emissivity [ 32 ] ), PCMs been widely applied in nonvolatile photonic applications, such as all‐photonic memories, [ 26,33,34 ] active absorbers, [ 35 ] filters, [ 25 ] lenses, [ 34,36 ] sensors, [ 36 ] displays, etc. [ 26,27,37–39 ] Among the above optical applications, the PCM‐based solid‐state reflective display [ 27 ] is a revolutionary display technology.…”
Section: Introductionmentioning
confidence: 99%